Head teachers’ perceptions about time spent on teaching and learning: A context from Nepal - Kunwar, Rajendra; Shrestha, Amrit Kumar; Poudel, Kamal Kumar; Phuyel, Shyam Prasad (Nurture, 2023)
Purpose: The study explores the perceptions of head teachers about time spent on teaching and learning in their schools. Specifically, the study investigates the headteachers’ perceptions of teacher-spent time (TST) in teaching and its implementation status in school-level education in Nepal. Design/Methodology/Approach: It is based on the qualitative descriptive survey research design. It was carried out with ten community school headteachers of the Ilam district as the sample. Six of them belonged to three rural municipal areas, and four were from two municipal areas. The sample for the study was drawn purposively. A semi-structured interview was used to collect the data from the headteachers as the respondents, and the data was analyzed by applying the thematic analysis technique under five themes. Findings: The result indicates that the disparity among the schools in terms of physical conditions and resources resulted in workload management problems, challenges with TST implementation, and weak supervision. Conclusion: It was concluded that the promotion of teacher awareness about their profession was necessary for effective TST implementation and the overall development of quality education. Limitations and Implications: The study uses only one variable-headteachers’ perceptions of TST and a small sample that may affect the generalizability of the result. So, it is suggested that a further study be conducted covering various dimensions of TST. Practical Implications: Despite these limitations, the study has a number of practical implications for the Nepalese education policy and practice as well as other contexts with a comparable set of circumstances. These include improving school leadership, enhancing teacher preparation, and addressing resource shortages to improve student learning outcomes. Contribution to Literature: The study can contribute to the literature on education by highlighting the perspectives of head teachers and providing insights into effective strategies for optimizing the amount of time spent on teaching and learning.